(untitled) (Al-Qamar, 2019)
This study discusses in detail the varied Quranic recitations in tafseer Aljlalian by Jalāl al-Dīn al-Maḥallī and Jalāl al-Dīn al-Suyūtī. The study begins with a brief about definition of recitations established categories. Terms and condition of Qirā’at, the study covers 19 controversial themes over which Quran differed due to their respective understanding of the varied recitations.